2022
DOI: 10.1101/2022.07.05.22277238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association meta-analysis of spontaneous coronary artery dissection reveals common variants and genes related to artery integrity and tissue-mediated coagulation

Abstract: Spontaneous coronary artery dissection (SCAD) is an understudied cause of acute myocardial infarction primarily affecting women. It is not known to what extent SCAD is genetically distinct from other cardiovascular diseases, including atherosclerotic coronary artery disease (CAD). Through a meta-analysis of genome-wide association studies including 1917 cases and 9292 controls of European ancestry, we identified 17 risk loci, including 12 new, with odds ratios ranging from 2.04 (95%CI 1.77-2.35) on chr21 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…The work presented by Tarr et al 16 in this Journal on the genetic architecture of SCAD has revealed novel insight into the rare monogenic and common polygenic underpinnings of this disease (Figure ). This report is an important addition of recent work in this area from wholeexome sequencing 17 and GWAS studies [10][11][12][13] which highlight the importance of genetic mechanisms influencing the onset of SCAD. With their report of ≈20% of patients with actionable genetic findings, it raises the important question on if genetic testing for SCAD should be integrated in the clinical practice.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The work presented by Tarr et al 16 in this Journal on the genetic architecture of SCAD has revealed novel insight into the rare monogenic and common polygenic underpinnings of this disease (Figure ). This report is an important addition of recent work in this area from wholeexome sequencing 17 and GWAS studies [10][11][12][13] which highlight the importance of genetic mechanisms influencing the onset of SCAD. With their report of ≈20% of patients with actionable genetic findings, it raises the important question on if genetic testing for SCAD should be integrated in the clinical practice.…”
Section: Discussionmentioning
confidence: 92%
“…In a series of GWAS studies in SCAD, 5 regions of the genome had been identified to meet genome-wide significance including 1q21.2 (C1orf51), 10,11 6p24.1 (PHACTR1/EDN1), [10][11][12] 12q13.3 (LRP1), 10,11 15q21.1 (FBN1), 11 and 21q22.11 (LINC00310). 10,11 This list of 5 loci has just recently been expanded in a new preprint, where Adlam et al 13 have revealed a meta-analysis of SCAD GWAS revealing 12 new loci, making a total of 17 loci to meet genome-wide significance for SCAD. Indeed, further population level genetic analysis with a polygenic risk score has confirmed that there are opposing genetic mechanisms between SCAD-related MI and atherosclerotic MI.…”
Section: Spontaneous Coronary Artery Dissection and The Intersection ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, hazard ratios (HRs) for this SCAD PRS are roughly similar to contemporary CAD PRS including millions of variants from genome-wide association studies with a few hundred associated gene regions. This may be expected as the HRs for all individually significant common variants for SCAD from only approximately 2000 cases to date are of larger effect sizes than all of those for CAD from approximately 200 000 cases . Of note, the current study did not use the latest SCAD genome-wide association study to prevent overfitting as the present study participants were included in that discovery study.…”
mentioning
confidence: 99%
“…As such, monogenic/mendelian inheritance in SCAD appears to be the exception rather than the rule . Instead, the underlying genetic susceptibility to SCAD likely arises secondary to oligogenic or polygenic inheritance caused by an increased burden of relatively common genetic variants, including 17 genetic loci identified via genome-wide association studies (GWAS) and a recent GWAS meta-analysis . As a result of the (1) low yield of pathogenic/likely pathogenic (P/LP) variants in CTD/arteriopathy-susceptibility genes and (2) potential danger of overinterpreting ambiguous variants of uncertain significance (VUS) in individuals without an extracoronary CTD/arteriopathy phenotype, the current consensus is to reserve genetic testing in SCAD for those cases where there is reasonable clinical suspicion for an underlying inherited CTD/arteriopathy …”
mentioning
confidence: 99%